2012
DOI: 10.1136/bjsports-2012-091127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ethnicity upon cardiovascular adaptation in competitive athletes: relevance to preparticipation screening

Abstract: Regular participation in intensive physical exercise is associated with several structural and electrophysiological cardiac adaptations that enhance diastolic filling and facilitate a sustained increase in the cardiac output that is fundamental to athletic excellence. Such cardiac adaptations are collectively referred to as the ‘Athlete's Heart’ and are frequently reflected on the 12-lead ECG and imaging studies. Thorough knowledge relating to exercise-associated cardiovascular adaptation is imperative for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…The most pronounced paradigm of ethnically distinct modifications stems from athletes of African/Afro-Caribbean descent, who exhibit a significantly higher prevalence of repolarization anomalies and left ventricular hypertrophy (LVH), posing significant challenges when differentiating physiological LVH from HCM. 6,7 For 2 years, our insitution has followed the model of systematic ECHO when screening all high-level athletes competing in Qatar (an ethnically diverse and heterogenous population). Accordingly, we sought to: (1) confirm the efficacy of systemic ECHO alongside the ECG, personal/family history questionnaires, and physical examination, as collective tools to identify diseases with the potential to cause SCD within our population of athletes; and (2) provide a cost-analysis of a government-funded pre-participation screening programme.…”
Section: Introductionmentioning
confidence: 99%
“…The most pronounced paradigm of ethnically distinct modifications stems from athletes of African/Afro-Caribbean descent, who exhibit a significantly higher prevalence of repolarization anomalies and left ventricular hypertrophy (LVH), posing significant challenges when differentiating physiological LVH from HCM. 6,7 For 2 years, our insitution has followed the model of systematic ECHO when screening all high-level athletes competing in Qatar (an ethnically diverse and heterogenous population). Accordingly, we sought to: (1) confirm the efficacy of systemic ECHO alongside the ECG, personal/family history questionnaires, and physical examination, as collective tools to identify diseases with the potential to cause SCD within our population of athletes; and (2) provide a cost-analysis of a government-funded pre-participation screening programme.…”
Section: Introductionmentioning
confidence: 99%
“…The extremes of LVH seen in athletes (beyond 13 mm in men and 12 mm in women) overlap with that seen in patients with morphologically mild HCM 11. Thus, an athlete with LVH beyond 13 mm represents a grey zone between physiological adaptation and mild expression of HCM, although LVH of up to 16 mm has been shown in black athletes, which again highlights the difficulty of interpreting wall thickness measurements in making the distinction between pathology and athletic remodelling 12. Various criteria for making this distinction have been described, including the degree of LVH, patterns of LVH and left ventricular cavity size (table 2).…”
Section: Challenges In the Differentiation Of The Athlete's Heart Vermentioning
confidence: 98%
“…6,117,[225][226][227][238][239][240][241][242] Notably, ethnic and racial differences are underscored by Magalski et al, 225 who found potentially pathological patterns in ECGs in 30% of black professional football players compared with only 13% of whites, a difference that was independently associated with race. T-wave inversions in anterior leads V 1 through V 4 have been cited as unique ethnic variants in the ECGs that occur in male athletes of African/Afro-Caribbean origin.…”
Section: Race and Sexmentioning
confidence: 99%
“…T-wave inversions in anterior leads V 1 through V 4 have been cited as unique ethnic variants in the ECGs that occur in male athletes of African/Afro-Caribbean origin. 239 241 Therefore, screening ECGs can be influenced by racial distribution, which can potentially inflate false-positive rates 89,225,227,[238][239][240][241][242] ; this resonates for African and other black athletes, in whom left ventricular wall thickness can exceed that of white athletes. 238,240 These factors could potentially trigger a cascade of unfortunate events that would generate an overdiagnosis of HCM, as well as unfair and unnecessary disqualification from competitive sports.…”
Section: Race and Sexmentioning
confidence: 99%